Age-related prey selectivity and foraging efficiency in Olrog's Gulls Larus atlanticus feeding on crabs in their non-breeding grounds. - Beron, Maria Paula (2011)
Foraging ecology is an essential component of the life history of a species and a good understanding of foraging ecology is especially important for threatened species where prey populations may be adversely affected by anthropogenic processes. This study examines age-related prey selection and prey-handling efficiency of Olrog's Gulls (Larus atlanticus) during the non-breeding season at the Mar Chiquita Coastal Lagoon, Argentina. Foraging behaviour and diet were determined by focal observation and compared with the availability of prey within their foraging patches. All captured prey were crabs, with the Burrowing Crab (Neohelice granulata) more commonly taken than the Mud Crab (Cyrtograpsus angulatus). Gulls consumed small and medium-sized crabs in higher proportions than those available and consumed more male crabs. Juvenile Gulls had longer handling times than older birds. Handling times increased with size of crabs independently of the sex of prey. The handling efficiency of adults was significantly higher than that of subadults, which in turn was higher than that of juveniles. These differences between age-classes could be attributed to differential foraging skills and social subordination of juvenile Gulls. The reasons for avoidance of large crabs is not certain but might be because carapaces are not easily digested, there is a higher risk of injury, or or capture of large crabs may result in more intense kleptoparasitic interactions, among others. © 2011 Royal Australasian Ornithologists Union.